Antibacterial effect of genetically-engineered bacteriophage ϕEf11/ϕFL1C(Δ36)PnisA on dentin infected with antibiotic-resistant Enterococcus faecalis. (October 2017) - Tinoco, Justine Monnerat; Liss, Nadia; Zhang, Hongming; Nissan, Roni; Gordon, Wanda; Tinoco, Eduardo; Sassone, Luciana; Stevens, Roy
Highlights: Treatment of E. faecalis- infected dentin with bacteriophage ϕEf11/ϕFL1C(Δ36)P nisA resulted in a decrease in the residual bacterial population. Both vancomycin-sensitive and resistant E. faecalis strains were disrupted by infection with bacteriophage. The recovered E. faecalis titer was reduced by 18% for the JH2-2 infected models, and by 99% for the V583 infected models. Abstract: Objective: Enterococcus faecalis is a gram-positive facultative anaerobic bacterium, which is present in 30–89% of teeth with postendodontic treatment failures. E. faecalis is capable of penetrating dentinal tubules and surviving as a monoculture after conventional endodontic therapy, indicating that it is resistant to commonly used endodontic disinfection protocols. Different E. faecalis strains have shown resistance to several antibiotics, and have been associated with both dental pathology and systemic infections. The aim of this study was to evaluate the efficacy of a genetically engineered bacteriophage to disinfect dentin infected with antibiotic resistant strains of E. faecalis. Methods: Extracted human dentin root segments were cemented into sealable two-chamber devices, fabricated from syringe needle caps to form in vitro infected-dentin models. The models were inoculated with an overnight suspension of either E. faecalis V583 (vancomycin resistant strain) or E. faecalis JH2-2 (fusidic acid and rifampin resistant, vancomycin sensitive strain). After 7 days of incubation at 37 °C, a suspension of a genetically engineered phage, ϕEf11/ϕFL1C(Δ36)P nisA, was added to the root canal of each infected dentin segment, and the incubation was continued for an additional 72-h. Dentin was harvested from the walls of each root canal and assayed for the residual titer of E. faecalis cells. Results: The recovered E. faecalis titer was reduced by 18% for the JH2-2 infected models, and by 99% for the V583 infected models. Conclusion: Treatment: of E. faecalis- infected dentin with bacteriophage ϕEf11/ϕFL1C(Δ36)P nisA consistently resulted in a decrease in the residual bacterial population of both vancomycin-sensitive and resistant strains.